Characteristics of student cultural intelligence in East Priangan and counseling services to facilitate it - Nugraha, Agung; Supriatna, Mamat; Suherman, Uman; Budiman, Nandang; Imaddudin, Aam (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
The current era of Society 5.0 and high accessibility has an impact on the dynamics of academic life in higher education, namely the increasingly diverse characters and backgrounds of students’ lives. Cultural competency for students in conditions like this becomes a necessity. This research aims to reveal the characteristics of students' cultural intelligence in East Priangan, including in terms of gender differences. Apart from that, another aim of this research is also to formulate counseling services to facilitate the optimization of students’ cultural intelligence. A cross-sectional study was used to reveal the cultural intelligence characteristics of 417 students in East Priangan. Accidental sampling was used in this research. Data collection uses the Cultural Intelligence Scale (CQS). The analysis technique uses a central symptom measure to describe the characteristics of students' cultural intelligence and Pearson correlation to measure the relationship between its aspects. Independent t test analysis was used to compare the characteristics of students' cultural intelligence based on gender. The result of the analysis are alpha 0,05; F=0,405; p =0,715. The results of the research show that the cultural intelligence of East Priangan students is moderate and there is no significant difference between male and female students. Recommendations for a counseling framework to facilitate the cultural intelligence of students in East Priangan which can be formulated based on the original values of stusdent life in East Priangan as well as multicultural competence for counselors who will use this framework.